When the FBI Knocks: Racialized State Surveillance of Muslims. (September 2019) - Alimahomed-Wilson, Sabrina
The sustained fixation on Muslims as the perennial suspects in domestic terrorism is a stereotype that continues to pervade counter-intelligence driven efforts. This research analyzes 113 cases of FBI contact with US Muslims living in Los Angeles, CA. Based upon these cases, this research suggests that every day, normal behavior becomes suspicious only when practiced by US Muslims, which would otherwise be acceptable, mundane, and unremarkable for ordinary white Christians, therefore constituting a form of "racialized state surveillance." The most prevalent questions asked by FBI agents to Muslims in this study were regarding religious practices or affiliation with religious organizations demonstrating the FBI faultily presumes that Muslim ties to their community and faith is abnormal, and worthy of state surveillance. This research reveals that FBI contact with Muslims is often not reliant upon actual indications of criminal activity, but instead the contact is predicated upon the suspicion of who is engaged in these behaviors. Under racialized state surveillance, these actions become hyperscrutinized and deemed worthy of FBI assessment.